2020
DOI: 10.3389/fpls.2020.00641
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Argonaute 5 Functions in Aphid–Plant Interaction

Abstract: Aphids feeding on plants experience similar responses to pathogens due to the prolonged and intimate contact with the plant. Diuraphis noxia is an economically important aphid pest on wheat that exhibits such an interaction. Studies on small RNA (sRNA) that regulate genes imparting resistance to wheat against D. noxia have predicted an Argonaute 5 (TaAGO5) gene as possible role player in the resistance response. Functional characterization revealed that TaAGO5 is crucial in regulating the response to infestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…ET and ABA had the strongest effect on the transcription of the AGO5 gene (Table 3). Recently, it was shown that AGO5 has a critical role in regulating the response against colonization by Diuraphis noxia since the knockdown of AGO5 in the resistant wheat line Tugela DN resulted in a fully susceptible phenotype [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ET and ABA had the strongest effect on the transcription of the AGO5 gene (Table 3). Recently, it was shown that AGO5 has a critical role in regulating the response against colonization by Diuraphis noxia since the knockdown of AGO5 in the resistant wheat line Tugela DN resulted in a fully susceptible phenotype [32].…”
Section: Discussionmentioning
confidence: 99%
“…sRNAs are generated by DCLs and function through AGOs to silence target genes [21]. The role of AGO1, AGO4, AGO5, DCL2, and DCL4 has been detected in the regulation of defense responses of Arabidopsis, cotton, and wheat against various aphid species [30][31][32][33]. Although the role of miRNAs in plant defense against insects has been established, the mechanisms of action and mechanisms of regulation of RNAi have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…AGO5 and, therefore, its cargo sRNAs play different physiological and developmental roles. For instance, AGO5 modulates part of the plant defense responses against the Potato virus X and aphids in A. thaliana and wheat, respectively ( Brosseau and Moffett, 2015 ; Sibisi and Venter, 2020 ). AGO5 also participates in the seed coat pigmentation in G. max ( Cho et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ago4 has been implicated in RNA-directed DNA methylation and chromatin is epigenetically modified by this pathway. Generally, through their small RNA partner, plant Ago proteins are also involved in antiviral or bacterial defense mechanisms as well as responses to herbivore attack ( Pradhan et al, 2017 ; Sibisi and Venter, 2020 ).…”
Section: Rnai Components In Animals and Plantsmentioning
confidence: 99%